Pengaruh Kerjasama Tim, Lingkungan Kerja, Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan KUD Pakis Kabupaten Malang - Mubarohk, Kharel; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the influence of teamwork, work environment, occupational safety, and health on employee performance at KUD Pakis, Malang Regency. The research adopts a quantitative approach, utilizing questionnaires to collect data from employees as respondents. Multiple linear regression analysis was applied to identify the simultaneous and partial effects of independent variables on employee performance. The results indicate that teamwork, work environment, and occupational safety and health have a significant positive impact on employee performance. Specifically, a supportive work environment and cohesive teamwork enhance productivity, while implementing comprehensive safety and health measures contributes to improved performance. These findings underscore the importance of strategic human resource management in fostering organizational success and ensuring employee well-being. Keywords: Teamwork, Work Environment, Occupational Safety And Health, Employee Performance